Attenuation of Aortic Aneurysms with Stem Cells from Different Genders - Davis, John P. (J Surg Res, 2015)
INTRODUCTION: No medical therapies are yet available to slow abdominal aortic aneurysm (AAA) growth. This study sought to investigate the effect of different genders of bone marrow derived mesenchymal stem cells (MSC) on AAA growth in a murine AAA model. Given the decreased rate of AAA in women, it is hypothesized that female MSC would attenuate AAA growth more so than male MSC. MATERIALS AND METHODS: Aortas of 8- to 10-week-old male C57Bl/6 mice were perfused with purified porcine pancreatic elastase to induce AAA formation. Bone marrow-derived MSC from male and female mice were dosed via tail vein injection (3 million cells per dose, 500 μL of volume per injection) on post-aortic perfusion days 1, 3, and 5. Aortas were harvested after 14 days. RESULTS: Mean aortic dilation in the elastase group was 121±5.2% (mean±SEM), while male MSC inhibited AAA growth (87.8±6.9%, P=0.008) compared to elastase. Female MSC showed the most marked attenuation of AAA growth (75.2±8.3% P= 0.0004). Pro-inflammatory cytokines tumor necrosis factor α (TNF-α), interleukin-1β (IL-1β), and macrophage chemotactic protein-1 (MCP-1) were only decreased in tissues treated with female MSC (p=0.017, p=0.001, and p<0.0001, respectively when compared to elastase). CONCLUSIONS: These data exhibit that female MSC more strongly attenuate AAA growth in the murine model. Furthermore, female MSC and male MSC inhibit proinflammatory cytokines at varying levels. The effects of MSC on aortic tissue offer a promising insight into biologic therapies for future medical treatment of AAAs in humans.